In2O3 Based Hybrid Materials: Interplay between Microstructure, Photoelectrical and Light Activated NO2 Sensor Properties - Abulkosim Nasriddinov; Sergey Tokarev; Olga Fedorova; Ivan Bozhev; Marina Rumyantseva (Chemosensors, 2022)
In this work, organic–inorganic hybrids based on nanocrystalline indium oxide and ruthenium (II) heteroleptic complexes were used as sensitive materials for room temperature light-activated NO2 detection. In2O3 was obtained by chemical precipitation method and then annealed at three different temperatures (T = 300, 500, 700 °C) in order to investigate the influence of the microstructure of indium oxide on sensor characteristics of hybrid materials and on kinetics of the rise and fall of photoconductivity. The results of the X-ray phase analysis demonstrated that the obtained materials are single-phase with a cubic bixbyite structure. The Ru (II) heteroleptic complex, which was used as a photosensitizer, made it possible to shift the optical sensitivity range of the hybrids to the low energy region of the spectrum and to use a low-power LED (λmax = 470 nm) source for the photoactivation process. The sensor properties were investigated toward NO2 at sub-ppm range at room temperature. It was found that for pure oxides, the sensor signal correlates with a specific surface area, while for hybrid materials, both the sensor signal and photoresponse increase with increasing the matrix crystallinity. In this case, the main role is played by traps of nonequilibrium charge carriers, which are structural defects in the matrix.